Continuum models of focused electron beam induced processing - Toth, Milos; Lobo, Charlene; Friedli, Vinzenz; Szkudlarek, Aleksandra; Utke, Ivo (Beilstein Journal of Nanotechnology, 2015)
Focused electron beam induced processing (FEBIP) is a suite of direct-write, high resolution techniques that enable fabrication and editing of nanostructured materials inside scanning electron microscopes and other focused electron beam (FEB) systems. Here we detail continuum techniques that are used to model FEBIP, and release software that can be used to simulate a wide range of processes reported in the FEBIP literature. These include: (i) etching and deposition performed using precursors that interact with a surface through physisorption and activated chemisorption, (ii) gas mixtures used to perform simultaneous focused electron beam induced etching and deposition (FEBIE and FEBID), and (iii) etch processes that proceed through multiple reaction pathways and generate a number of reaction products at the substrate surface. We also review and release software for Monte Carlo modeling of the precursor gas flux which is needed as an input parameter for continuum FEBIP models.
Keywords: continuum model; deposition; electron beam processing; etching; gas injection system